Pengaruh Profitability, Liquidity, Firm Size, Dan Leverage Terhadap Cash Holding Perusahaan Manufaktur - Davidson, Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to examine the influence of profitability, liquidity, firm size, dan leverage towards cash holding in manufacturing companies listed on Indonesia Stock Exchange in period of 2016-2018. The technique of sample selection is using purposive sampling method and the data source of this research is a secondary one and obtained a 74 sample manufacuring companies. The analytical method used in this research is a regression analysis of panel data with fixed effect model using E-Views software of version 10. The results of this research show that firm size have no effect and negative on cash holding, while profitability, liquidity, and leverage has effect and positive effect on cash holding.